2022 Practice Recommendation Updates From the World Consensus Conference on BIA-ALCL. (26th May 2022) - Santanelli di Pompeo, Fabio; Clemens, Mark W; Atlan, Michael; Botti, Giovanni; Cordeiro, Peter G; De Jong, Daphne; Di Napoli, Arianna; Hammond, Dennis; Haymaker, Cara L; Horwitz, Steven M; Hunt, Kelly; Lennox, Peter; et al.
Abstract: Background: Laboratory and clinical research on breast implant–associated anaplastic large cell lymphoma (BIA-ALCL) is rapidly evolving. Changes in standard of care and insights into best practice were recently presented at the 3rd World Consensus Conference on BIA-ALCL. Objectives: The authors sought to provide practice recommendations from a consensus of experts, supplemented with a literature review regarding epidemiology, etiology, pathogenesis, diagnosis, treatment, socio-psychological aspects, and international authority guidance. Methods: A literature search of all manuscripts between 1997 and August 2021 for the above areas of BIA-ALCL was conducted with the PubMed database. Manuscripts in different languages, on non-human subjects, and/or discussing conditions separate from BIA-ALCL were excluded. The study was conducted employing the Delphi process, gathering 18 experts panelists and utilizing email-based questionnaires to record the level of agreement with each statement by applying a 5-point Likert Scale. Median response, interquartile range, and comments were employed to accept, reject, or revise each statement. Results: The literature search initially yielded 764 manuscripts, of which 405 were discarded. From the remaining 359, only 218 were included in the review and utilized to prepare 36 statements subdivided into 5 sections. After 1 round, panelists agreed on all criteria. Conclusions: BIA-ALCL is uncommon and still largely underreported. Mandatory implant registries and actions by regulatory authorities are needed to better understand disease epidemiology and address initial lymphomagenesis and progression. Deviation from current diagnosis and treatment protocols can lead to disease recurrence, and research on breast implant risk factors provide insight to etiology. Level of Evidence: 4: